CONCERNING IMPROVEMENT OF THE QUALITY OF NOTARY SERVICES - Konussova Венера Тулеутаевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2017)
In this article, the author examines the possibility of enhancing the quality of notarial actions through improvement in three key areas: - Revision of the procedure and conditions for access to the profession of notary; - Professional development and methodological support for the notarial actions; - Tightening of liability for negligent performance of notary functions. Through the analysis of the current legislation and international experience, the author has formulated some proposals aimed at improving the performance of notary actions. Specific conclusions and suggestions of the author are reduced to the revision of eligibility requirements for candidates to perform notarial actions and to ensuring the effectiveness of the internship through a revision of the requirements for its program. As the necessary measure to enhance the level of professional knowledge of notaries, it is proposed to organize the mandatory refresher course. Such an obligation, in the author’s opinion, should be legally established and imposed both on territorial Notary Chambers and on notaries themselves. In order to ensure uniformity of notarial practice the author emphasizes the need of common guidelines for certain notarial actions, which should be mandatory for notaries. There is a suggestion to revise approaches to the notaries’ liability. In particular, it is stipulated to involve notaries to disciplinary responsibility for violation of the Notary Code of Honor. In this case, the supreme measure of disciplinary liability could be an exclusion from the Chamber of Notaries. In order to improve the existing model of insurance of civil liability of notaries, it is proposed to provide risk insurance obligation of the notaries’ professional liability under the contracts of individual and collective security. At the same time one of the main principles of the insurance should be full protection of proprietary interests, which implies differentiation of insurance payments. The results of this research can be used in the legislative work on the improvement of notarial actions in the Republic of Kazakhstan.